Effect of mentha extract (Mentha piperita) supplementation in drinking water on performance, plasma lipoproteins, carcass charasteristic and liver color index or weight in broiler chickens - Abdulkarim, Rahim; Aghazadeh, Ali Mirza; Daneshyar, Mohsen (The Indian Journal of Animal Sciences, 2012)
Mixed day-old broiler chicks (160) in 4 groups were used to investigate the effects of mentha extract (Mentha piperita) on performance, carcass characteristics, plasma lipoproteins and liver indices. All the chickens were fed the similar starter (day 1–21 of age) and grower (day 22–42 of age) diets in pellet form, but received 0.0 (ZM), 0.2 (LM), 0.4 (MM) and 0.6% (HM) alcoholic extract of Mentha piperita in drinking water during the experimental period (day 1 to day 42 of age). Performance (feed intake, body weight gain and feed conversion ratio), hot carcass and proportional weights of thigh, wing and abdominal fat were not affected by mentha consumption. But breast proportional weight increased linearly as the mentha extract level increased. Positive and negative quadratic regression models were observed between mentha extract level with the liver colour index and liver proportional weight respectively. Mentha extract supplementation decreased plasma total cholesterol, triglyceride, LDL- C and VLDL- C quadrically. It was concluded that mentha extract consumption in drinking water can have beneficial effects on plasma lipoproteins and breast proportional weight. Moreover it decreased the synthesis of lipids in liver and consequently decreased the liver proportional weight and increased the liver colour index.